Formation of Graded TiO2 Layer on Ti Wire by Direct Alternating Current Discharge Plasma at Atmospheric Pressure - Yoshimi Watanabe; Naho Mitsuishi; Motoko Yamada; Hisashi Sato; Seigo Takashima; Eri Miura-Fujiwara (Metals)
Although metallic materials have been used as load-bearing materials in dental and biomedical fields since they have good mechanical properties such as good ductility and strength, their aesthetic properties are inferior to those of ceramic or resin. To obtain aesthetically improved Ti dental devices, the formation of white titanium oxide on pure Ti dental devices was studied. Direct atmospheric pressure plasma (APP) treatment using alternating current was carried out on pure a Ti plate and wire. It was found that a titanium oxide layer with enough whiteness can be obtained on pure Ti wire using direct APP treatment. Although delamination of the titanium oxide layer was found after a bending test, the concept of functionally graded materials (FGMs) can overcome the shortcoming.